Tinjauan Viktimologis Terhadap Tindak Pidana Perdagangan Orang (Human Trafficking) - Rahmat Hi Abdullah (JURNAL YUSTIKA: MEDIA HUKUM DAN KEADILAN, 2019)
Victims are an important element in the continuation of legal evidence as a victim witness or reporter. As is the case with the problem of human trafficking crime. Victimology with its various kinds of views extends the criminal etiological theories needed to understand the existence of crime as a better structural and non-structural victimization. besides the views in viktimology encourage people to pay attention and serve each party who can be victims of mental, physical, and social. From the explanation of the victim's typology and the factors that led to the crime of trafficking in persons, it was concluded that there were three types of victims of trafficking in persons, namely Latend or Prodisposed Victims who were economic contributors. Participating Victims were victims who because the cause is a low education factor, and False Victims which is being a victim because the cause is a consumptive behavior factor.